Family Support vs. Family Strain: Determining Aggression Pathways in Adolescents from Bandung - Novya Ashlahatul Mar'ah; Wini Hadiyani; Tira Arrahman (STIKep PPNI Jawa Barat, 2025)
Background: Aggressive behavior remains a significant concern during adolescence, a developmental period marked by emotional instability and social adjustment. Family functioning is known to shape adolescents’ emotional regulation and behavioral outcomes. However, evidence regarding how family function relates to aggressive tendencies among Indonesian adolescents remains limited. Objective: This study aimed to analyze the relationship between family function and aggressive behavior in adolescents. Methods: A cross-sectional correlational design was used involving 140 students recruited using convenience sampling at SMK Bina Warga Bandung. Data were collected using two validated instruments: the Family Assessment Device (FAD) to assess family functioning and the Buss-Perry Aggression Questionnaire (BPAQ) to measure aggressive behavior. Data analysis was performed using the Pearson correlation test. Results: The mean score for family function was 141.06 ± 9.73, indicating generally good family functioning. Meanwhile, the mean score for aggressive behavior was 77.32 ± 4.51, with hostility as the highest-scoring domain. Pearson correlation analysis revealed a significant negative relationship between family function and aggressive behavior (r = –0.287, p < 0.001), indicating that adolescents who perceive their family functioning as better tend to exhibit lower levels of aggression. Conclusion: Family function plays a crucial protective role in reducing aggressive behavior among adolescents. Interventions that enhance family communication, emotional support, and collaborative problem-solving may effectively prevent aggression and promote healthy adolescent development. Further research incorporating longitudinal designs and broader socio-cultural variables is recommended.